The Effect of Being Overweight and Obesity on Self-Confidence Levels Among Teenagers at State High School 22 in Jakarta and A Review from an Islamic Perspective - Mutia Sa’idah; Mirfat Mirfat; Sri Wuryanti; M. Fazlurrahman Anshar (Interdisciplinary Social Studies, 2026)
Overweight and obesity among adolescents have become significant public health concerns because they not only increase the risk of physical diseases but also affect psychological well-being, particularly self-confidence. This study aimed to determine the relationship between overweight and obesity status and self-confidence levels among adolescents at State High School 22 Jakarta and to review the findings from an Islamic perspective. This study employed an analytical survey design with a cross-sectional approach. The population consisted of students in grades X and XI at State High School 22 Jakarta, with 128 respondents selected using a purposive sampling technique based on predefined inclusion and exclusion criteria. Data were collected through Body Mass Index (BMI) measurements and the Self-Confidence Scale questionnaire. Data analysis was performed using univariate analysis and the Fisher’s exact test with the assistance of SPSS software. The results showed that most respondents were categorized as overweight (43.8%), followed by obesity class I (39.1%) and obesity class II (17.2%). Most adolescents demonstrated high self-confidence levels (64.8%). Statistical analysis revealed a significant relationship between overweight and obesity status and self-confidence levels among adolescents (p = 0.005). From an Islamic perspective, physical conditions do not determine human dignity, as every individual is created in the best form by Allah SWT. Therefore, adolescents with overweight or obesity require holistic support involving physical health management, psychological assistance, and spiritual strengthening to develop positive self-acceptance and self-confidence.